Sharia Bank Research Roadmap in Indonesia - Edy Suprianto; Dedi Rusdi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The study describes the roadmap for the history of sharia bank research in Indonesia from 12 accredited journals in Indonesia with a minimum index of Sinta 2. The sample from 2011 to 2021 obtained 83 articles discussing sharia bank. Based on the results of the analysis, the majority of research on Islamic banks in Indonesia is published in two journals, namely the Iqtishadia journal (Jurnal of Islamic Economics and Business Studies) and Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), with 31% and 22% of the total sample article for each journal. 18 out of 83 articles obtained are qualitative research methods. Meanwhile, 65 articles use quantitative methods. In qualitative research, descriptive analysis methods or case studies are the most widely used, and in quantitative research, the most commonly used method is regression analysis.